Dataset of Irrigation Scheme Research - Sok, Sao; Klok, Sam Ang; Sithirith, Mak (2025)
The data was collected in two of Cambodia’s Mekong Delta Provinces including Prey Veng and Takeo, as well as in Kampong Thom-a province located in the Tonle Sap Lake (TSL) region. The researchers utilized both qualitative and quantitative methods to gather primary and secondary data from the studied sites. The primary data were obtained through household interviews, key informant interviews (KIIs) and focus group discussions (FGDs).